2020
DOI: 10.1093/molbev/msz311
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA Evidence from China Reveals the Expansion of Pacific Dogs

Abstract: The ancestral homeland of Australian dingoes and Pacific dogs is proposed to be in South China. However, the location and timing of their dispersal and relationship to dog domestication is unclear. Here, we sequenced 7,000- to 2,000-year-old complete mitochondrial DNA (mtDNA) genomes of 27 ancient canids (one gray wolf and 26 domestic dogs) from the Yellow River and Yangtze River basins (YYRB). These are the first complete ancient mtDNA of Chinese dogs from the cradle of early Chinese civilization. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 41 publications
4
46
0
Order By: Relevance
“…In order to investigate haplogroup patterns and dynamics, ggplot2 [58], a data visualization package in R [59], was used to create a graphical representation of the proportions of haplogroup through time. The plot included the ancient Eurasian dogs from this study and those available in the literature [6,9,10,13,29,31,33,34,52,[60][61][62][63][64] (Table S1).…”
Section: Haplotype Identification and Phylogenetic Analysesmentioning
confidence: 99%
“…In order to investigate haplogroup patterns and dynamics, ggplot2 [58], a data visualization package in R [59], was used to create a graphical representation of the proportions of haplogroup through time. The plot included the ancient Eurasian dogs from this study and those available in the literature [6,9,10,13,29,31,33,34,52,[60][61][62][63][64] (Table S1).…”
Section: Haplotype Identification and Phylogenetic Analysesmentioning
confidence: 99%
“…Shisanhang (Taiwan) is one of two samples from the region and is considered the root of the network [19].…”
Section: Comparison Of Dingo Mtdna Genomesmentioning
confidence: 99%
“…Australian mtDNA type of the canine A1b4 subhaplogroup. This southeastern type has been proposed to originate in southern China and includes dogs from Papua New Guinea [19,22].…”
Section: Phylogenetic and Network Analyses Show That Dingo Cooinda Ha...mentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it difficult to harvest the target DNA of ancient remains through the conventional method of PCR amplification. One possible alternative to PCR amplification is target enrichment via DNA hybridization capture, a well‐tested method for obtaining DNA data from bones of ancient humans (Haak et al, 2015; Liu et al, 2021; Wang et al, 2019; Yang et al, 2020), ancient animals (Wen et al, 2022; Zhang, Sun, et al, 2020), and environmental sediments (Massilani et al, 2022; Schulte et al, 2021; Slon et al, 2017; Zhang, Xia, et al, 2020). However, to our knowledge, no studies on aDNA capture from wood remains have reported using this method so far (Orlando et al, 2021; Wagner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%